2016
DOI: 10.1016/j.egja.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia of ultrasound guided rectus sheath catheters versus continuous wound catheters for colorectal surgery: A randomized clinical trial

Abstract: 2016) Postoperative analgesia of ultrasound guided rectus sheath catheters versus continuous wound catheters for colorectal surgery: A randomized clinical trialAbstract Purpose: The purpose of this study was to evaluate the postoperative analgesia and morphine requirements of ultrasound guided rectus sheath catheters versus continuous wound catheters in midline open colorectal surgery patients. Methods: Sixty patients of both sexes aged 40-65 years were randomized into 2 equal groups to receive postoperative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…One RCT. 8 investigated the effect of bilateral rectus sheath block compared with continuous wound infiltration. Basic analgesia was not given and no difference between either modality was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One RCT. 8 investigated the effect of bilateral rectus sheath block compared with continuous wound infiltration. Basic analgesia was not given and no difference between either modality was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Qazi et al 7 also reported reduced postoperative opioid consumption with TAP block. One RCT 8 . investigated the effect of bilateral rectus sheath block compared with continuous wound infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…Internal organ injury 0 (0%) 0 (0%) -Systemic toxicity 0 (0%) 0 (0%) -G general anaesthesia; GR Bilateral rectus sheath block combined with general anaesthesia plane of the transverse abdominis muscle, entered the rectus abdominis sheath, and distributed on the surface of the skin [18]. The main process of RSB is to inject local anaesthetics between the rectus abdominis and the posterior sheath of the rectus abdominis [19]. Therefore, RSB exerted a good effect in terms of perioperative analgesia for median abdominal incisions [20].…”
Section: Discussionmentioning
confidence: 99%
“…Bashandy reported that anterior branches of the T7-T12 thoracic nerve and the L1 lumbar nerve travelled through the plane of the transverse abdominis muscle, entered the rectus abdominis sheath, and distributed on the surface of the skin [18]. The main process of RSB is to inject local anaesthetics between the rectus abdominis and the posterior sheath of the rectus abdominis [19].…”
Section: Discussionmentioning
confidence: 99%